Muhayyelden musavvere: Matbuat çağında Osmanlı'da Afrika tasavvuru (Sudan örneği) - KOÇYİĞİT, ÖMER (My University, 2022)
On dokuzuncu yüzyılda yaşanan toplumsal ve düşünsel köklü değişimler matbaa faaliyetlerinin gelişmesiyle doğrudan ilgilidir, zira matbuatın yaygınlaşması bilginin dolaşımı ve küreselleşme açısından önemli bir rol oynadı. Uzak memleketlerdeki olaylar telgraf yoluyla kısa sürede öğrenildi, yeni bilgi ve haberler matbu yayınlar vesilesiyle gündem oluşturmaya başladı. Bu etkinin görüldüğü alanlardan biri Osmanlı Devleti’nin Afrika ile olan ilişkileridir. Bugüne kadar Osmanlı’da on dokuzuncu yüzyılda Afrika’ya dair ilgi ve malumatın artması genellikle siyasi yönelimle, imparatorluk hedefleri ve İttihad-ı İslam gibi politikalarla yorumlanageldi. Bu makale, Osmanlı-Afrika ilişkilerindeki bu yoğun irtibatın sadece siyasi hedeflerle açıklanamayacağını, Hint ve Uzak Doğu Asya ile olan ilişkilerde de görüldüğü gibi, matbuat devriminin burada kilit bir rol oynadığını savunmaktadır. Zira matbuat faaliyetlerinin en önemli hizmeti insanların bilgilerini, algılarını ve gündemlerini belirlemek oldu. Osmanlı’da Afrika’yla ilgili Türkçe yazılmış ya da Türkçeye tercüme edilmiş eserleri inceleyen bu çalışma, özelde bu ilişkilerin bir yansıması olarak Sudan bölgesi hakkındaki kitap, dergi ve gazetelere yoğunlaşmaktadır. Matbuat devrimi öncesinde iki bölge halkının birbirleri hakkındaki algısına da değinerek bu çağın insanların tasavvurunda ne gibi etkiler meydana getirdiğini tartışmaktadır

One of the most fundamental changes that occurred in the nineteenth century was the development of printing, as the spread of printed works played an important role in the circulation of information and globalization. News about events that transpired in distant countries was spread via telegraph; as a result, information and news stories began to make an impact by means of printed publications. One particular example of such an impact concerns the relations between the Ottoman Empire and Africa. The increased interest and circulation of information on Africa in the nineteenth-century Ottoman Empire has predominantly been interpreted by modern historians in terms of political orientation, imperial goals and policies such as Pan-Islamism. This article argues that the bolstering of contact in Ottoman-African relations cannot be explained by political purposes alone. On the contrary, the printing revolution played a key role in this regard, as in the cases of Ottoman relations with India and Far East Asia, especially because the main contribution of printing has been to shape people’s knowledge, perceptions and agendas. By examining works about Africa that were written in Turkish or translated into Turkish in the Ottoman Empire, this study focuses on books and newspapers about the specific region of Sudan as a reflection of those relations. It also discusses the impact of the printing revolution on how the people, namely the Ottomans and the Africans, perceived each other differently before and after the spread of printing in the light of specific examples.
From imagining to envisioning: ottoman conceptions of africa in the age of print (the example of sudan)
Keywords: Ottoman Empire; Africa; Sudan; printing press; printed publications; Osmanlı Devleti; Afrika; matbaa; matbuat